FORMULASI DAN UJI STABLITAS FISIK GEL EKSTRAK BATANG PISANG MAULI (Musa acuminata) - Maman Diki Wahyudi; Fitri Syahrina; Amy Nindia Carabelly; Dewi Puspitasari; Yusrinie Wasiaturrahmah (Dentin, 2022)
ABSTRACTBackground: Mauli banana is a typical South Kalimantan banana. Mauli banana stems contain active substances, such as tannins, saponins, alkaloids, flavonoids, and lycopene. Several studies have shown that Mauli banana stem extract (BPM) has anti-inflammatory, antibacterial properties and reduces the viability of Streptococcus Mutans and Lactobacillus acidophilus in the formation of dual-species biofilms. Gel formulations must have physical stability to ensure the physical stability of the gel, gel quality, and meet the criteria parameters during storage. The physical stability test of the gel was investigated for 16 days at room temperature. Gel stability tests were homogeneity, dispersion, and pH tests. Objectives: to determine the formulation and physical stability including homogeneity, dispersibility, and pH test of BPM gel 25%; 37.5%; 50%, and 62.5%. Methods: Mauli banana stems were obtained from SMK-PP Banjarbaru, tested for determination, made extracts, and made BPM gel by adding propylene glycol, glycerin, Na-CMC, nipagin, and aquadest, then testing for homogeneity, spreadability, and pH. Results: BPM gel showed homogeneous results until the 16th day with even distribution of color and no coarse grains. The BPM gel dispersion test met the criteria of 3cm-5cm until the 16th day with the results of the BPM gel dispersive power being 3.7cm-4.6cm. In the pH test, the BPM gel also met the criteria until the 16th day with a physiological pH of the oral cavity of 5.5-7.9. Conclusion: BPM gel with a concentration of 25%; 37.5%; 50% and 62.5% have results that match the criteria based on homogeneity, dispersion, and pH. Keyword: Gel, Mauli Banana Stem Extract, Physical Stability ABSTRAK Latar Belakang: Pisang mauli merupakan pisang khas Kalimantan Selatan. Batang pisang mauli mengandung zat aktif, seperti tanin, saponin, alkaloid, flavonoid dan likopen. Beberapa penelitian ekstrak batang pisang mauli (BPM) memiliki khasiat sebagai antiinflamasi, antibakteri dan menurunkan viabilitas Streptococcus Mutans serta Lactobacillus achidophilus dalam pembentukan dual-spesisies biofilm. Pembuatan formulasi sebuah gel harus memiliki stabilitas fisik agar menjamin kestabilan fisik gel, kualitas gel dan memenuhi parameter kriteria selama penyimpanan. Uji stabilitas fisik gel diteliti selama 16 hari pada suhu ruangan. Pengujian stabilitas gel yang dilakukan ialah uji homogenitas, uji daya sebar dan uji pH. Tujuan: Mengetahui formulasi dan stabilitas fisik meliputi uji homogenitas, daya sebar dan pH gel ekstrak batang pisang mauli (Musa acuminata) konsentrasi 25%; 37,5%; 50% dan 62,5%. Metode: Batang pisang mauli diperoleh dari SMK-PP Banjarbaru, diuji determinasi, dilakukan pembuatan ekstrak dan pembuatan gel BPM dengan menambahkan propilen glikol, glycerin, Na-CMC, nipagin dan aquadest, selanjutnya gel dilakukan uji homogenitas, daya sebar dan pH. Hasil: Uji homogenitas menunjukan gel BPM semua konsentrasi homogen sampai hari ke-16 dengan meratanya penyebaran warna dan tidak terdapat butiran kasar. Uji daya sebar gel BPM memenuhi kriteria 3cm-5cm sampai hari ke-16 dengan hasil range daya sebar gel BPM 3,7cm-4,6cm. Pada uji pH gel BPM seluruh konsentrasi juga memenuhi kriteria sampai hari ke-16 dengan pH fisiologis rongga mulut 5,5-7,9. Kesimpulan: Gel ekstrak batang pisang mauli konsentrasi 25%; 37,5%; 50% dan 62,5% memiliki hasil yang sesuai dengan kriteria berdasarkan homogenitas, daya sebar dan pH. Kata kunci : Ekstrak Pisang Mauli, Gel, Stabilitas Fisik